(untitled) (PANGEEA, 2025)
Research about the age and geomorphological processes using the archaeological data in Alba Iulia area. Tried floodplain terrace age assessment using the methodology applying archaeological methods. Research refers to the middle basin of the Mures, namely the area between Sântimbru and Blandiana. In making paper we analyzed a vast archaeological documentary material, selecting items using purpose. The conclusion confirms that the predominantly alluvial floodplain terrace ended about 5000-6000 years ago, after rivers have exerted a dominant share of deepening, thus leading to an altitude of about 2,5-3,5 ma floodplain terrace.